2014
DOI: 10.1097/01.dss.0000452669.84787.bf
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 70% Glycolic Peels Versus 15% Trichloroacetic Peels for the Treatment of Photodamaged Facial Skin in Aging Women

Abstract: Superficial peels, such as 70% GA and 15% TCA, proved to be an effective treatment modality for photodamaged facial skin. Both acids contribute to improvement of the photodamaged skin's parameters. Glycolic acid increases skin's hydration faster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…Novel retinol formulations have also been the focus of attention . In contrast, only a couple of recent studies has compared the efficacy and tolerability of various chemical peels . Yet, the comparative effects of the 2 treatments on photo‐damaged skin have never been evaluated in a randomized controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…Novel retinol formulations have also been the focus of attention . In contrast, only a couple of recent studies has compared the efficacy and tolerability of various chemical peels . Yet, the comparative effects of the 2 treatments on photo‐damaged skin have never been evaluated in a randomized controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…Kubiak et al compared 70% GA with 15% TCA peels and found clinical improvement in hydration and elasticity parameters as well as improvement in UV-induced post-inflammatory pigmentation in both groups. However, patients' satisfaction rates for GA peels were higher because of a superior side effect profile [5] . Table 2 is a comparative table of other studies evaluating the use of glycolic acid chemical peels in the treatment of photoaging.…”
Section: Discussionmentioning
confidence: 99%
“…The above data indicate that lactic acid, applied in the right concentration and at the appropriate pH of the solution used, and thus ensuring adequate bioavailability, has a slightly lower possibility of penetration through the skin than glycolic acid and by acting more superficially is also a substance that causes significantly less irritation. In addition, lactic acid is a substance naturally present in the skin, part of the NMF, which contributes significantly to its more caring effect on the skin …”
Section: Characteristics Synthesis and Uses Of Lactic Acidmentioning
confidence: 99%